2002
DOI: 10.1007/s10126-002-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of the Channel Catfish Spleen: Analysis of Genes Involved in Immune Functions

Abstract: Both qualitative and quantitative patterns of tissue-specific gene expression can be determined using gene profiling. Expressed sequence tag (EST) analysis is an efficient approach not only for gene discovery and examining gene expression, but also for development of molecular resources useful for functional genomics. As part of an ongoing transcriptome analysis of channel catfish (Ictalurus punctatus), EST analysis was conducted for gene annotations and profiling using a complementary DNA library developed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…Jx14 was made from the catfish autonomous (immortal) macrophage cell line 42TA (Miller et al, 1994b). The spleen cDNA library was previously reported (Kocabas et al, 2002).…”
Section: Expression Of Nk-lysin Genesmentioning
confidence: 99%
“…Jx14 was made from the catfish autonomous (immortal) macrophage cell line 42TA (Miller et al, 1994b). The spleen cDNA library was previously reported (Kocabas et al, 2002).…”
Section: Expression Of Nk-lysin Genesmentioning
confidence: 99%
“…Currently, a lot of fish ESTs have been released from model fish and food fish species, but over 50% of the teleost ESTs were generated from model fish, such as zebrafish (Gong, 1999), medaka , and fugu (Jaillon et al, 2004). Only a few of specific tissues have become the object of EST projects from some aquaculture species, such as winter flounder (Douglas et al, 1999), Japanese flounder (Inoue et al, 1997), salmon (Davey et al, 2001;Martin et al, 2002), channel catfish (Karsi et al, 1998Ju et al, 2000;Kim et al, 2000;Kocabas et al, 2002), red sea bream (Chen et al, 2004), tilapia (Shiue et al, 2004), common carp (Kono et al, 2004), and gilthead sea bream (Sarropoulou et al, 2005). The lack of EST resources in commercial fish species prohibits use of modern functional genomic approaches for the study of growth, development, reproduction, stress biology and molecular breeding (Chen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Three clones of channel catfish NK-lysin cDNA were initially identified from analysis of expressed sequence tags (ESTs) [28]. Sequence alignment revealed that all three cDNAs were transcripts from a single gene.…”
Section: Cmentioning
confidence: 99%